MALDI imaging mass spectrometry as a novel tool for detecting histone modifications in clinical tissue samples. (3rd March 2016) - Lahiri, Shibojyoti; Sun, Na; Buck, Achim; Imhof, Axel; Walch, Axel
SUMMARY: Histone post-translational modifications (PTMs), histone variants and enzymes responsible for the incorporation or the removal of the PTMs are being increasingly associated with human disease. Combinations of histone PTMs and the specific incorporation of variants contribute to the establishment of cellular identity and hence are potential markers that could be exploited in disease diagnostics and prognostics and therapy response prediction. Due to the scarcity of suitable antibodies and the pre-requirement of tissue homogenization for more advanced analytical techniques, comprehensive information regarding the spatial distribution of these factors at the tissue level has been lacking. MALDI imaging mass spectrometry provides an ideal platform to measure histone PTMs and variants from tissues while maintaining the information about their spatial distribution. Discussed in this review are the relevance of histones in the context of human disease and the contribution of MALDI imaging mass spectrometry in measuring histones in situ .